P138 I don't know, let's try some canestan: an audit of non-specific balanitis treatment and outcomes. (23rd May 2012) - Powles, E; Marsden, R; Gupta, N K; Green, T
Abstract : Background: Balanoposthitis commonly presents to Genitourinary Medicine and may be caused by a wide variety of unrelated conditions. The 2008 UK National Guideline on the Management of Balanoposthitis recommends biopsy to exclude malignant disease where clinical diagnosis is uncertain and balanitis persists for more than 6 weeks despite simple treatment. Method: A retrospective audit of case notes with KC60 code C6c presenting between January and June 2011. Results: 90 patients were diagnosed with balanitis (age range 16–71 years, mean 30, mode 22, median 25). 68 cases were treated as presumed candidal balanitis with either Clotrimazole cream, Fluconazole or Daktacort. In the remaining cases no presumptive diagnosis was made but 10 patients were given empirical Trimovate cream, three had Metronidazole tablets, one had Dermovate cream and one had Betnovate cream. Seven patients did not receive any medication. In all but one case the balanitis had fully resolved within 6 weeks. In the persistent case, initial treatment was with Clotrimazole cream for presumed Candida; when the lesions persisted this was changed to Daktacort but a clear diagnosis was not made. However, he failed to attend for further follow-up so it is not known if the balanitis resolved with the change of treatment. No cases were referred for biopsy. Conclusion: The rate of persistent balanitis was extremely low in this cohort and all except one case resolved with treatment. This patient did not return for further review and was not referred for biopsy. Penile biopsy is recommended where the balanitis persists and the diagnosis remains unclear as in this case. A robust system of recall management is needed to ensure that appropriate action is taken in such cases.